Strategi Pengembangan dan Daya Dukung Berkelanjutan Kawasan Ekowisata The Lodge Maribaya - Marhanah, Sri; Sukriah, Erry; Juniardi, Agripa; Harto, Budi (Journal of Indonesian Tourism, Hospitality and Recreation, 2023)
ABSTRACTThe management of The Lodge Maribaya, which is a tourist destination and a protected forest area, must be able to strike a balance between its two main responsibilities to ensure the comfort of tourists and the sustainability of the environment. This maintenance effort should give attention to the activities of visitors. As well as tourism sustainability refers to the quality of tourism activities, environmental quality, tourist satisfaction and the impact on environmental damage. The purpose of this study was to determine the capacity of correction factor and the maximum load capacity of The Lodge Maribaya. This study uses scientific methods related to Physical Carrying Capacity (PCC), Actual Carrying Capacity (ACC) and Effective Carrying Capacity (ECC), with a sample of 20 respondents. The results show that a PCC of 1304 can physically adjust, a ACC of 389 with an adjustment factor and an ECC of 311 exceeding the maximum visiting capacity, and the number of daily visits in 2021 will be 55. The Lodge Maribaya area physically, ecological aspects and management skills are still suitable with the average number of visitors.ABSTRAKPengelolaan The Lodge Maribaya, yang merupakan tujuan wisata dan kawasan hutan lindung, harus dapat mencapai keseimbangan antara dua tanggung jawab utamanya untuk memastikan kenyamanan wisatawan dan keberlanjutan lingkungan. Upaya pemeliharaan ini harus memperhatikan dan aktivitas pengunjung. Serta keberlanjutan pariwisata mengacu pada kualitas tempat kegiatan pariwisata, kualitas lingkungan dan kenyamanan, kepuasan wisatawan serta dampaknya terhadap kerusakan lingkungan. Tujuan dari penelitian ini adalah untuk mengetahui faktor koreksi kapasitas beban dan kapasitas beban maksimum The Lodge Maribaya. Penelitian ini menggunakan metode ilmiah yang berkaitan dengan Physical Carrying Capacity (PCC), Actual Carrying Capacity (RCC) dan Effective Carrying Capacity (ECC), dengan sampel 20 responden. Diperoleh hasil bahwa PCC sebesar 1.304 dapat menyesuaikan secara fisik, RCC sebesar 389 dengan faktor penyesuaian dan ECC sebesar 311 melebihi kapasitas kunjungan maksimal, serta jumlah kunjungan harian pada tahun 2021 menjadi 55. Kawasan The Lodge Maribaya secara fisik, aspek ekologi dan keterampilan pengelolaan masih sesuai dengan rata-rata jumlah pengunjung.